Faktor Stress dan Pola Makan pada Guru Obesitas di SMA Kota Kendari - La Banudi; Wenny Ino Ischak; Suriana Koro; Purnomo Leksono (Politeknik Kesehatan Kemenkes Mamuju, 2018)
Obesity in adolescents (aged> 18 years) showed an increase. In the male gender, Riskesdas 2007 increased by 12% to 13% in Riskesdas in 2010 and 19% in 2013. In women Riskesdas higher Riskesdas 2007 ie by 13%, rising to 20% in 2010 and 28 RiskesdasRiskesdas% in 2013.the aim of this study was to the relationship betwen stressfactor and dietery habit with Obesity on senior high school teacher in Kendar Monicipalityi. Type of study is cross-sectional study. The research location is all the high school in Kendarimonicipality that as many as 12 SMA. The population is a high school teacher in the city of Kendari recorded and is still active as a teacher. The sample was a high school teacher Public and Private many as 250 people. The sampling technique sampling techniques purporsive. Data analysis was performed univariate and bivariate using Chi Square test. This study has received ethical health research Medical Faculty of Hasanuddin University, No. UH16070578. The results of the study are the characteristics of respondents in this study, for the age group as many as 128 people (51.2%) group> 45 years of age, sex, ie as many as 155 people (62.0%) women, work husband / wife as much as 127 oang (50, 8%) work in the private sector. Statistically significant relationship antaa stress with obesity (pv = 0.005 or X2h = 8.065) and there is a relationship between diet and obesity (pv = 0.013 or X2h = 6.175).